2022
DOI: 10.3389/fmars.2021.807493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Targets of Transcription Factor WRINKLED1-Like Related to Lipid Biosynthesis From Marine Microalga Dunaliella parva

Abstract: WRINKLED1 (WRI1) is an important transcription factor controlling lipid biosynthesis. To elucidate the function of Dunaliella parva WRI1-like (WRI1-like) (i. e., DpWRI1-like), the targets of DpWRI1-like were identified by chromatin immunoprecipitation sequencing. The results showed that DpWRI1-like regulated many target genes involved in carbohydrate metabolism, lipid metabolism, photosynthesis, and transcription factor. It was proposed that DpWRI1-like participated in a regulatory network controlling lipid bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Under nitrogen and sulfur starvation conditions, 694 genes were found to be involved in TAG accumulation and stress responses. Shen et al (2021) also performed ChIP-Seq experiments: using the Motif Alignment and Search Tool, two motifs (TGTGTGTGTGTG and ACACACACACAC) were identified that would be of interest to conduct further research on to study the regulation mechanism of WRINKLED1 (WRI1) TF ( Bailey et al, 2009 ; Shang et al, 2022 ). The WRI1 TF in Arabidopsis thaliana was shown to regulate many target genes involved in carbohydrate and lipid metabolism ( Maeo et al, 2009 ; Shang et al, 2022 ).…”
Section: Transcription Factors-based Metabolic Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…Under nitrogen and sulfur starvation conditions, 694 genes were found to be involved in TAG accumulation and stress responses. Shen et al (2021) also performed ChIP-Seq experiments: using the Motif Alignment and Search Tool, two motifs (TGTGTGTGTGTG and ACACACACACAC) were identified that would be of interest to conduct further research on to study the regulation mechanism of WRINKLED1 (WRI1) TF ( Bailey et al, 2009 ; Shang et al, 2022 ). The WRI1 TF in Arabidopsis thaliana was shown to regulate many target genes involved in carbohydrate and lipid metabolism ( Maeo et al, 2009 ; Shang et al, 2022 ).…”
Section: Transcription Factors-based Metabolic Engineeringmentioning
confidence: 99%
“…Potential regulatory pathways have been proposed for some of the TFs tabulated in Table 2 . To elucidate the mechanism of underlying lipid production associated with specific TF expression, some studies have examined the genes potentially regulated by these TFs using experimental methods ( Bajhaiya et al, 2016 ; Goncalves et al, 2016 ; Jia et al, 2022 ; Jia et al, 2019 ; Takahashi et al, 2021 ; Shang et al, 2022 ; Shi M et al, 2022 ). For example, Gargouri et al (2015) combined omics (transcriptomic, proteomic, and metabolomic) analysis to identify transcriptional regulatory networks corresponding to oil accumulation under nitrogen deprivation in C. reinhardtii ( Gargouri et al, 2015 ).…”
Section: Transcription Factors-based Metabolic Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, DpWRI1-like regulates target genes related to carbohydrate metabolism (including genes related to photosynthesis, glycolysis, the tricarboxylic acid cycle, and starch metabolism) to enhance the conversion of sugars to lipids. On the other hand, DpWRI1-like regulates target genes related to lipid metabolism (especially genes involved in fatty acid biosynthesis, such as KAS) to promote lipid production [101]. In addition, the transcription factors DpAP2 and WRKY were identified as associated with carotenoid synthesis in Dunaliella sp.…”
Section: Other Microalgaementioning
confidence: 99%